2020
DOI: 10.7573/dic.2020-5-3
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab: an alternative therapy for idiopathic chronic eosinophilic pneumonia with glucocorticoid intolerance

Abstract: A 55-year-old woman with cough-variant asthma presented for 1 month of worsening wheezing, cough, and dyspnea refractory to treatment. Initial laboratory findings revealed profound peripheral eosinophilia, and a chest computed tomography showed bi-apical consolidation. Bronchio-alveolar lavage demonstrated alveolar eosinophilia. She was diagnosed with idiopathic chronic eosinophilic pneumonia (ICEP). Her peripheral eosinophilia and respiratory symptoms improved rapidly with high-dose systemic corticosteroid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(28 reference statements)
0
9
0
1
Order By: Relevance
“…However, it is not only ineffective for RA but also an anti-IL-5 agent that sometimes develops arthritis by reducing the concomitant glucocorticoid dose. [ 12 ] Similarly, anti-IgE antibodies can also reduce glucocorticoid doses, but their effects are limited to cases with high IgE levels. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not only ineffective for RA but also an anti-IL-5 agent that sometimes develops arthritis by reducing the concomitant glucocorticoid dose. [ 12 ] Similarly, anti-IgE antibodies can also reduce glucocorticoid doses, but their effects are limited to cases with high IgE levels. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not only ineffective for RA but also an anti-IL-5 agent that sometimes develops arthritis by reducing the concomitant glucocorticoid dose. [12] Similarly, anti-IgE antibodies can also reduce glucocorticoid doses, but their effects are limited to cases with high IgE levels. [13] Baricitinib, originally developed for the treatment of RA, inhibits cytokine signaling, including IL-6, IL-12, IL-20, IL-22, IL-23, and IFN-γ, but also exerts regulatory effects on the Th2 cytokines such as IL-4, IL-5, and IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…Allen and Wert conducted an open-label, retrospective study of the treatment of CEP with mepolizumab and found that treatment with mepolizumab was associated with a reduction in disease episodes, steroid use, and improvement in pulmonary infiltrates on imaging [ 25 ]. Mepolizumab and dupilumab have been reported to improve symptoms and reduce relapse rates and have a corticosteroid-sparing effect (CEP) [ 26 ]. Patients treated for asthma with dupilumab may develop serious systemic eosinophilia, such as eosinophilic pneumonia or vasculitis in the sense of EGPA.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the present cases, all 4 ICEP patients with frequent recurrences were well controlled by anti-IL-5 agents, and no patients have developed relapses after the treatment, as supported by previous single-case reports. [32][33][34][35][36] Ricketti et al also reported that a patient with relapsing CEP was treated with benralizumab, and the safety of long-term treatment for over 30 months was found, with maintenance of its efficacy. 37 In addition, corticosteroid treatment was withdrawn or reduced in all 4 cases, which contributed to attenuation of corticosteroid-related adverse effects (Table 3).…”
Section: Dovepressmentioning
confidence: 97%